The Role of Self-Efficacy in Career Adaptability: A Comparative Study of Senior and Vocational High School Students - Rizki Amalia; Muhammad Syarif Hidayatullah (Edunesia : Jurnal Ilmiah Pendidikan, 2026)
Career development during adolescence requires psychological resources that enable students to manage educational and occupational transitions. However, empirical evidence comparing self-efficacy and career adaptability across academic and vocational secondary education remains limited. This study examined the relationship between self-efficacy and career adaptability, compared these variables between senior high school (SMA) and vocational high school (SMK) students, and assessed the contribution of self-efficacy to career adaptability. A quantitative cross-sectional survey was conducted with 224 Indonesian secondary school students recruited through convenience sampling, with participant recruitment exhibiting snowball characteristics. Data were collected using the General Self-Efficacy Scale (GSES) and the Career Adapt-Abilities Scale (CAAS) and analyzed using descriptive statistics, Pearson correlation, independent-samples t-test, and simple linear regression. Self-efficacy was positively associated with career adaptability (r = 0.824, p < 0.001) and explained 67.8% of its variance (R² = 0.678, p < 0.001). Vocational high school students demonstrated significantly higher self-efficacy and career adaptability than senior high school students. These findings highlight the importance of strengthening self-efficacy through school-based career guidance interventions.